Economic Conditions at Birth, Birth Weight, Ability, and the Causal Path to Cardiovascular Mortality - Gerard J. van den Berg; Bitte Modin (Institute for the Study of Labor (IZA), 2013)
We analyze interaction effects of birth weight and the business cycle at birth on individual cardiovascular (CV) mortality later in life. In addition, we examine to what extent these long-run effects run by way of cognitive ability and education and to what extent those mitigate the long-run effects. We use individual records of Swedish birth cohorts from 19151929 covering birth weight, family characteristics, school grades, sibling identifiers, and outcomes later in life including the death cause. The birth weight distribution does not vary over the business cycle. The association between birth weight (across the full range) and CV mortality rate later in life is significantly stronger if the individual is born in a recession. This is not explained by differential fertility by social class over the cycle. Ability itself, as measured at age 10, varies with birth weight and the cycle at birth. But the long-run effects of early-life conditions appear to mostly reflect direct biological mechanisms. We do not find evidence of indirect pathways through ability or education, and the long-run effects are not mitigated by education.
Keywords: I10; I12; I21; I31; J10; J13; N34; C41; E32; 330; longevity; genetic determinants; health; business cycle; life expectancy; cardiovascular disease; school grades; siblings; fetal programming; cause of death; life course; developmental origins; nature and nurture; cognitive ability; education; stratified partial likelihood; recession; Herzkrankheit; Sterblichkeit; Erwachsene; Konjunktur; Geschichte; Geburt; Kinder; Gesundheit; Schweden